North Atlantic Regional Water Resources Study. Appendix Q. Erosion and Sedimentation. - ECONOMIC RESEARCH SERVICE WASHINGTON D C (1972)
The purpose of this study is to make an appraisal of the erosion and sedimentation problems in the North Atlantic Region. The Appendix defines erosion and sedimentation problems and discusses the areal distribution, magnitude, variability and projections of future erosion and sedimentation problems for the years 1980, 2000 and 2020.F. The effects of erosion and sedimentation on agriculture, municipal and industrial water supplies, reservoirs, transportation facilities, recreation, and fish and wildlife are discussed. Erosion and sediment damages in dollars are estimated. Appendix Q to report dated Jun 72, AD-A036 616. See also Appendix R, AD-A036 638.